A three-dimensional morpho-volumetric similarity study of Down syndrome keratopathy vs. keratoconus - Ibrahim Toprak; Francisco Cavas; José S. Velázquez; Jorge L. Alio del Barrio; Jorge L. Alio (Eye and Vision)
Abstract Background To compare and contrast morpho-volumetric features between Down syndrome (DS) cornea and non-DS keratoconic cornea by three-dimensional (3D) modelling. Methods Forty-three subjects (43 eyes) with DS and 99 patients matching their age and sex (99 eyes) with keratoconus (KC) were included in this single-center cross-sectional study. Main outcome measures were high-order aberrations (HOA), central corneal thickness (CCT), spherical equivalent refraction, and morpho-volumetric parameters established using a 3D corneal model, such as deviation of anterior and posterior corneal apices (Dapexant/Dapexpost) and minimum thickness points (Dmctant/Dmctpost) from corneal vertex, areas of the anterior and posterior surfaces (Aant/Apost), sagittal area passing through the anterior and posterior corneal apices (Aapexant/Aapexpost) and minimum thickness point (Amctpost) and corneal volume of the complete cornea (Vtotal). Results Age, gender, spherical equivalent refraction, CCT and Vtotal were similar between the net on-DS KC and DS groups (P > 0.05), while non-DS KC group had higher HOA than the DS group (P < 0.05). Dapexant, Aant, Apost and Aapexant showed higher values in the DS group than in the non-DS KC group, whereas Dapexpost showed a reduction in the DS group when compared with the non-DS KC group (P < 0.05). Conclusions This study demonstrated that anterior and posterior corneal apex dynamics were specifically different in DS subjects, as the anterior apex tends to displace more prominently when compared to that from the non-DS KC group, while the posterior apex appears to be more stable than that in non-DS KC, which also support the theory that DS patients suffer from a specific keratopathy, distinctively different to KC but strongly related to it, and probably showing a diversity of corneal phenotypes in all cases of DS.